Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises: 41

Answer

y=-1

Work Step by Step

Simplifying 5(2y + -3) = 3(7y + -6) + 19(y + 1) + 14 Reorder the terms: 5(-3 + 2y) = 3(7y + -6) + 19(y + 1) + 14 (-3 * 5 + 2y * 5) = 3(7y + -6) + 19(y + 1) + 14 (-15 + 10y) = 3(7y + -6) + 19(y + 1) + 14 Reorder the terms: -15 + 10y = 3(-6 + 7y) + 19(y + 1) + 14 -15 + 10y = (-6 * 3 + 7y * 3) + 19(y + 1) + 14 -15 + 10y = (-18 + 21y) + 19(y + 1) + 14 Reorder the terms: -15 + 10y = -18 + 21y + 19(1 + y) + 14 -15 + 10y = -18 + 21y + (1 * 19 + y * 19) + 14 -15 + 10y = -18 + 21y + (19 + 19y) + 14 Reorder the terms: -15 + 10y = -18 + 19 + 14 + 21y + 19y Combine like terms: -18 + 19 = 1 -15 + 10y = 1 + 14 + 21y + 19y Combine like terms: 1 + 14 = 15 -15 + 10y = 15 + 21y + 19y Combine like terms: 21y + 19y = 40y -15 + 10y = 15 + 40y Solving -15 + 10y = 15 + 40y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-40y' to each side of the equation. -15 + 10y + -40y = 15 + 40y + -40y Combine like terms: 10y + -40y = -30y -15 + -30y = 15 + 40y + -40y Combine like terms: 40y + -40y = 0 -15 + -30y = 15 + 0 -15 + -30y = 15 Add '15' to each side of the equation. -15 + 15 + -30y = 15 + 15 Combine like terms: -15 + 15 = 0 0 + -30y = 15 + 15 -30y = 15 + 15 Combine like terms: 15 + 15 = 30 -30y = 30 Divide each side by '-30'. y = -1 Simplifying y = -1
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.